Dimensi Komunikasi Sebagai Pendorong Dinamika Soliditas Sosial Pada Masyarakat Hindu Di Kota Mataram - I Nengah Aryanatha (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2020)
This research is intended to examine the dimensions of communication as a driver of the occurrence of the dynamics of social solidity in the Hindu community in the city of Mataram. The design of this study is descriptive quality in order to find the substance related to the role of communication in influencing the dynamics of social solidity. Based on the results of the study it was found that the dynamics in social solidity that occur among Hindus in the city of Mataram communication became a driving force in realizing the dynamics of social solidity that was based on the existence of messages conveyed through the media or directly. First, this communication can be a driver to improve the quality of education which in turn leads to changes in religious social life. Second, communication also has a very important role in cultural adaptation. In this case through communication cultural adjustments occur, namely external cultures that enter the culture of the local community. Third, communication in managing the implementation of religious ceremonies has embodied modern patterns of organizational communication. In the implementation of religion the organizational communication process has a very important role in realizing the implementation of effective and efficient activities. Fourth, transcendent communication concerning the relationship between Hindus and worshiped God. In this case there is a tendency that the dynamics of social solidity in Hindu society in Mataram City are influenced by transcendent communication which is more personal in nature. This is what distinguishes it from the historical period, namely the implementation of religion is emphasized more togetherness aspects through joint activities that can encourage social ties.